Particle collector and preparation method thereof
By optimizing the raw material ratio and preparation process of the DPF particle trap, the problem of cordierite material generating specified channel specifications in high-temperature synthesis is solved, and the comprehensive performance improvement of low back pressure, thermal stability and high-efficiency filtration is achieved.
Patent Information
- Application Number
- CN202411620616.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
When existing DPF particle traps generate channels of specified specifications in high-temperature synthetic cordierite materials, it is difficult to take into account the requirements of thermal stability, structural strength and low back pressure, resulting in limited fuel economy and power performance.
By optimizing the raw material ratio, low backpressure DPF particle traps with a median pore size of 18um±3um, porosity of 55%~65%, and thermal expansion coefficient ≤1.0×10-6/℃ were prepared.
It realizes that while meeting the requirements of emission regulations, reduce the back pressure of DPF, improve filtration efficiency, enhance thermal stability and mechanical strength, thereby improving the overall performance and reliability of DPF.
Smart Images

Figure CN119140081B_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to the technical field of DPF particulate traps, and in particular to a particulate trap and a preparation method thereof. Background Art
[0002] Particulate matter is one of the most important pollutants in diesel engine exhaust emissions. In order to meet the strict PM and PN emission requirements, the diesel particulate filter DPF is currently recognized as an effective post-treatment device that can effectively eliminate diesel engine exhaust particulate matter.
[0003] The "Two-in-One" technology on the particulate filter is to coat the SCR catalyst in the DPF carrier, integrating the SCR and DPF functions into one, which can effectively reduce costs and reduce the installation space of the system. However, compared with the traditional DPF structure based on CDPF regeneration technology and FBC regeneration technology, the DPF based on the "Two-in-One" technology requires a larger porosity and average pore diameter.
[0004] Due to the FBC regeneration technology, the heat release speed is fast, which has a great thermal impact on the DPF. In this case, the heat capacity of the DPF is generally increased by reducing the mesh number, increasing the wall thickness, and reducing the porosity and average pore diameter, thereby reducing its maximum temperature and temperature gradient when the engine enters the idle operation (Drop in Idle) state.
[0005] CDPF technology is to coat the filter with an oxidation catalyst, which can effectively reduce the temperature during DPF regeneration and help improve fuel economy. A small amount of oxidation catalyst coating can achieve a catalytic oxidation effect, and the general coating amount is (5~10) g / L. Therefore, the DPF using CDPF technology only needs a moderate porosity and average pore diameter.
[0006] The "two-in-one" technology, also known as SDPF, is to coat the reduced catalyst on the filter. The coating amount of the reduced catalyst must be many times higher than that of the oxidized catalyst to achieve the catalytic reduction effect. The coating amount is often as high as (90~220) g / L or even higher. This will inevitably lead to an increase in the pressure difference of the DPF and worsen fuel economy. Therefore, the DPF using the "two-in-one" technology requires a higher porosity and pore size to meet the requirements of high coating amount and low back pressure, and can effectively prevent the micropores on the wall from being blocked, avoiding affecting the exhaust gas from the engine's combustion out of the cylinder.
[0007] Specifically, as attached Figures 1 to 3As shown, since the existing cordierite DPF is a wall-flow structure, that is, a cross-hole plugging method, the airflow passes through the internal pore walls of the honeycomb ceramic for airflow and particle capture, rather than the airflow directly reaching the lower end surface from the upper end surface of the cylinder. Therefore, if too much catalyst is coated on the internal pore wall, it will occupy the micron-level micropores in the pore wall, affecting the airflow, resulting in engine exhaust obstruction, incomplete fuel combustion, and affecting engine power.
[0008] However, how to generate pores of specified specifications in high-temperature synthesized cordierite materials while ensuring thermal stability and structural strength stability is a considerable challenge for those skilled in the art. Summary of the invention
[0009] One of the purposes of the present invention is to provide a particulate filter and a preparation method thereof, which adjusts the pore size and porosity of the DPF particulate filter based on the research of the DPF particulate filter while meeting the requirements of the emission particulate matter control under the new emission regulations, and also takes into account the heat shock resistance.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0011] In a first aspect, the present invention provides a particle trap, comprising a particle trap body and a catalytic coating coated on the particle trap body, wherein the particle trap body comprises the following raw materials in percentage by mass: 70% to 80% of synthetic cordierite raw powder, 15% to 20% of a composite pore former, 2% to 6% of a binder, and 1% to 5% of a lubricating additive;
[0012] The composite pore-forming agent comprises white carbon black, crystalline silicon powder, pregelatinized starch powder and paraffin powder, and the ratio of white carbon black, crystalline silicon powder, pregelatinized starch powder and paraffin powder is 10:7.5:1.5:1.
[0013] The principle analysis of each raw material and the ratio relationship in the above formula is as follows:
[0014] Cordierite raw powder is the main structural material of DPF. After synthesizing cordierite, it has good mechanical strength and thermal stability and can maintain structural integrity under high temperature environment. Cordierite raw powder combined with composite pore former can form honeycomb ceramics with the desired pore structure. The amount of synthetic cordierite raw powder added needs to match the amount of pore former to ensure sufficient porosity and pore size. Here, the volume ratio model calculation or gradient experiment can be used to obtain a reasonable range of values.
[0015] The high proportion of 70% synthetic cordierite raw powder ensures the structural stability of DPF in long-term use, and the low thermal expansion coefficient of synthetic cordierite raw powder helps DPF maintain performance and dimensional stability in repeated thermal cycles, reducing the risk of thermal cracking and fatigue damage.
[0016] Preferably, the white carbon black is selected from EXP4215~1 low-density hollow "white carbon black", which can provide larger pores on the one hand, which helps to reduce the back pressure of DPF, and on the other hand, helps to form the required pore size distribution and improve the filtration efficiency. However, white carbon black is silicon dioxide, which is hollow, has limited pore-forming ability, and will affect the extrusion fluidity of the system. Excessive use may increase the difficulty of the blank making process and affect the material strength. The white carbon black in the present invention can also be replaced by spheroidized natural high-carbon graphite.
[0017] Crystalline silicon powder (fused crystallized silica powder) undergoes phase change during high temperature sintering, which will produce certain pores, which can refine the pore size, help to achieve precise pore size requirements, improve the stability of DPF materials at high temperatures, help to achieve a median pore size of 18um±3um, optimize filtration performance, and increase the service life of DPF in high temperature environments. Crystalline silicon powder needs to be used in conjunction with other pore formers to control pore size and porosity.
[0018] Pregelatinized starch powder decomposes during the sintering process to form micropores, which helps to increase the porosity. Pregelatinized starch can be decomposed at a relatively low temperature without damaging the cordierite structure, which helps to increase the porosity of the DPF and improve the filtration efficiency. However, the residue after decomposition may affect the thermal stability of the material, so it needs to be added in an appropriate amount.
[0019] The wax powder volatilizes during the sintering process, which not only helps to form a uniform pore structure, but also helps to mix and shape the raw materials. The uniform pore structure helps to improve the filtration performance and back pressure performance of the DPF. At the same time, the addition of wax powder also helps to improve the molding of the raw materials and facilitate production. Since the wax powder will volatilize at high temperatures, its dosage needs to be controlled to avoid affecting the pore structure.
[0020] The above raw materials and proportions are used to prepare a medium pore size of 18um±3um, a porosity of 55%~65%, and a thermal expansion coefficient (room temperature~800℃) ≤1.0×10 -6 / ℃ low back pressure DPF particulate filter. By precisely controlling the ratio of each raw material, the back pressure can be reduced while ensuring the filtration efficiency, and the thermal stability and mechanical strength can be improved, thereby improving the overall performance and reliability of the DPF. The advantage of this ratio is that it can balance the various performance indicators of the DPF, making it perform well in the harsh engine exhaust treatment environment.
[0021] The composite pore-forming agent used in the present invention can combine the advantages of different pore-forming agents to achieve better performance. Among them, low-density hollow "white carbon black" and unmelted crystalline silica powder can form larger pores, while pregelatinized starch powder and paraffin powder can form smaller pores. By reasonably adjusting the ratio between them, the pore size distribution can be controlled to meet the median pore size requirement of 18um±3um required by the present invention.
[0022] In addition, white carbon black and unmelted crystalline silica powder can also reduce the density and porosity of the material, while pregelatinized starch powder and paraffin powder can increase the porosity of the material. Through the above-mentioned ratio relationship, the porosity can be controlled within 55%~65%.
[0023] Unmelted crystalline silica powder and pregelatinized starch powder not only have good thermal stability, but also can ensure that DPF has good structural stability under high temperature environment. At the same time, low-density hollow "white carbon black" and unmelted crystalline silica powder have good shape retention ability and strength, which can improve the strength and toughness of DPF.
[0024] Through the combination of different pore formers, the pore size can be controlled to reach a median pore size of 18um±3um. The ratio of pore formers to pore plugging materials determines the final porosity of 55%~65%.
[0025] The invention realizes the balance of pore size, porosity and thermal expansion coefficient through reasonable raw material ratio, and meets the use requirements of DPF.
[0026] In some achievable embodiments, the pore size of the particle collector body is controlled within a median pore size range of 18um±3um, the porosity is 55%~65%, and the thermal expansion coefficient (room temperature~800℃) is ≤1.0×10 -6 / ℃.
[0027] And / or, the coating amount of the reducing catalyst in the catalytic coating is 120 g / L to 220 g / L.
[0028] In some achievable embodiments, the cordierite comprises the following raw material components in weight ratio: 35% to 45% of flaky talc, 15% to 25% of alpha alumina, 1% to 10% of activated alumina, 20% to 40% of kaolin, and 3% to 10% of silica powder;
[0029] And / or, the D50 of the flaky talc is 12um~27um, the D50 of alpha alumina is 0.5um~8um, the D50 of activated alumina is 1.5um~10um, and the D50 of kaolin is 2.5um~7.5um;
[0030] And / or, the activated alumina may be selected from at least one of diaspore, boehmite and aluminum hydroxide;
[0031] And / or, the kaolin is washed, peeled and calcined before use.
[0032] Before adding the pore-forming agent, the mixing and reaction of the above raw materials will have the following effects on the pore size distribution of the initial synthetic cordierite raw powder:
[0033] The flake structure of talc will form certain interlayer gaps during the stacking process, and these gaps constitute the initial pores of the material to a certain extent. However, since the stacking of talc is relatively dense, the pores formed are small in size and relatively evenly distributed.
[0034] When granular alpha alumina is mixed, it will form voids between particles in the material. The size of these voids depends on the size of the alumina particles (D50 is 0.5um~8um). Its distribution in the material will make the initial pore size distribution present a certain randomness, but no large pores will be formed as a whole.
[0035] Activated alumina releases gas during decomposition, which forms tiny pores inside the material. These pores are evenly distributed, but due to the relatively low content of activated alumina (1%~10%), the impact on the overall pore size distribution is limited, and the main effect is to increase the microscopic porosity inside the material.
[0036] The treated kaolin has a certain plasticity, and can fill part of the larger pores formed by other raw materials during the molding process, making the pore size distribution more uniform. At the same time, the shrinkage of kaolin itself during the drying and sintering process will also affect the pore size, which helps to form smaller and more uniform pores.
[0037] Filling silica powder between other raw material particles will reduce the gaps between particles, causing the initial pore size distribution to shift toward smaller pore sizes and making the pore size distribution more concentrated.
[0038] Through the above-mentioned formula system of synthetic cordierite raw powder, using different particle size combinations and different proportions, before adding the pore-forming agent, the initial pore size distribution of the initial synthetic cordierite raw powder is controlled to maintain it within a suitable pore size range, which is convenient for further optimization by the pore-forming agent in the later stage, and the pore size distribution in the initial state is not easy to be too large, which will cause a sharp change in heat resistance.
[0039] The synthesis steps of the above-mentioned synthetic cordierite raw powder are as follows:
[0040] (1) Raw material preparation: Select flaky talc raw materials with a D50 of 12um~27um, screen, magnetically separate and pre-treat to remove impurities; select alpha alumina raw materials with a D50 of 0.5um~8um to ensure that their quality and particle size meet the requirements;
[0041] Select at least one of diaspore, boehmite or aluminum hydroxide as the raw material of activated alumina according to the needs, control D50 at 1.5um~10um, and inspect the raw materials to ensure their activity;
[0042] The kaolin is washed, peeled and calcined to remove impurities and improve its purity and plasticity; silica micropowder raw materials with appropriate particle size (D50 between 3um and 10um) are selected to ensure its quality.
[0043] (2) Ingredients: Accurately weigh the raw materials according to the weight ratio of 35%-45% of flaky talc, 15%-25% of alpha alumina, 1%-10% of activated alumina, 20%-40% of kaolin, and 3%-10% of silica powder, and place them in a clean mixing container.
[0044] (3) Mixing: Use mechanical stirring equipment to fully stir the raw materials at an appropriate speed. The stirring time is determined according to the amount of raw materials and the stirring effect, and is generally not less than 30 minutes to ensure that the raw materials are mixed evenly.
[0045] (4) Pre-reaction: In order to make the raw materials react better, the mixed raw materials can be pre-reacted at a certain temperature (such as 400°C~600°C) for 1~2 hours. This step can promote the initial reaction between the raw materials and is conducive to the subsequent formation of the cordierite phase.
[0046] (5) Crushing and grinding: If the material after the pre-reaction has agglomeration phenomenon, it can be crushed and ground to crush the material to the required particle size range to ensure the uniformity of the particle size of the synthetic cordierite raw powder, which is beneficial to the subsequent molding process.
[0047] Through reasonable raw material ratios and synthesis steps, the complete formation of the cordierite crystal structure is ensured. The cordierite material has good thermal stability and can maintain the stability of its structure and performance under the high-temperature working environment of the particle collector (such as high temperatures during sintering and use), and will not cause deformation or damage to the material due to factors such as thermal expansion.
[0048] The reasonable combination of raw materials such as talc flakes and alpha alumina and the process control during the synthesis process make the cordierite material have high mechanical strength, including compressive strength and flexural strength. During the use of the particle collector, it can withstand external forces such as gas pressure, particle collision and vibration to maintain structural integrity.
[0049] And / or, the binder is selected from at least one of anionic polyvinyl alcohol and hydroxypropyl methylcellulose. The binder decomposes during high-temperature sintering, removes bound water at 400°C-800°C, and forms a dense structure with a certain strength. The cellulose organic binder begins to decompose after 180°C and is basically completely decomposed at 400°C. The process needs to maintain a low oxygen state to prevent the decomposition from being too concentrated, resulting in excessive heat release, and causing a large internal and external temperature difference. The product is subject to a large temperature difference and cracking.) These binders can effectively prevent the DPF material from breaking and wearing during the extrusion molding process. The binder here needs to be appropriate to avoid excessively increasing the viscosity of the material and affecting molding.
[0050] And / or, the lubricating additive is selected from at least one of glycerol, potassium laurate, and sodium stearate, which has the function of moisturizing and lubricating, and can improve the molding performance, sintering performance, and mechanical properties of the material. For example, glycerol can reduce the viscosity of the mud, and potassium laurate can emulsify the oil additive to form a good dispersion effect, and it also has certain lubricating properties. However, excessive lubricating additives may affect the drying and sintering process.
[0051] By optimizing the formula and raw material ratio, it is possible to produce a product with a median pore size of 18um±3um, a porosity of 55%~65%, and a thermal expansion coefficient (room temperature~800℃) ≤1.0×10 -6 / ℃ honeycomb ceramic products meet the use requirements of DPF and have the following functions:
[0052] 1. Reduce back pressure: High porosity and larger median pore size can reduce the airflow resistance of DPF, thereby reducing back pressure and improving engine fuel economy.
[0053] 2. Efficient capture of particulate matter: Appropriate porosity and narrow pore size distribution can effectively capture particulate matter and meet emission regulations.
[0054] 3. Resistance to heat shock: High structural strength, low elastic modulus and low thermal expansion coefficient can ensure that DPF has good structural stability and performance in high temperature environment.
[0055] In a second aspect, the present invention provides a method for preparing a low back pressure DPF particulate trap with a median pore size of 18um±3, which is used to prepare the above-mentioned particulate trap, and the preparation method comprises the following steps:
[0056] (1) Raw material mixing: The synthetic cordierite raw powder, composite pore former, binder and lubricating additive are mixed according to the proportion and mixed in a low-speed mixer to ensure that the raw materials are evenly distributed. Evenly distributed raw materials are the key to ensuring the consistency of the performance of the final product.
[0057] (2) Wet molding: Add an appropriate amount of water to the mixed raw materials, the conductivity of the water is lower than 0.056us / cm, stir evenly to form a mud block, and then form it by extrusion or pressing. The moisture content is controlled at 20%~30% and the molding pressure is appropriate. Wet molding helps to form a molded DPF green body with a certain shape and strength. The moisture content and pressure affect the molding quality and pore structure.
[0058] (3) Drying: The formed DPF sintered body is placed in a drying chamber for drying to remove moisture. This can prevent cracking or deformation caused by rapid evaporation of moisture during the subsequent sintering process and ensure the structural integrity of the DPF.
[0059] (4) Hole plugging: After drying, the DPF green body is preliminarily processed into regular size, and then the hole plugging material is used to cross-plug the holes on its two end faces. A carbon dioxide laser source is used to identify the low-viscosity, high-transmittance resin tape sealed on the end face and then separate the holes. The above-mentioned hole plugging material is "scraped" into the hole with a depth of 3.5~7mm to form a DPF green body to be sintered.
[0060] It should be noted that the plugging part is a fixed structure and does not change with the length and diameter of the product. Generally, the plugging depth is controlled at 3.5-7mm on one side. The function of the plugging material and the bonding strength with the main body require that the CTE curve of the plugging material should be similar to that of the main body and be able to complete its own sintering in the same sintering curve of the main body.
[0061] Here, it is necessary to complete preliminary calculations on the DPF green body to be sintered, calculate the external dimensions that offset the sintering size changes, and then process them, complete the injection of plugging materials, and form the DPF green body to be sintered through drying.
[0062] The pore forming requirements of the plugging material are that the pore forming requirements do not need to be consistent with the main body in this method. The porosity of the plugging material can be controlled at 30%-55%, and the pore size distribution requirements can be distributed in the range of 5um-15um.
[0063] In some achievable methods, the pore-blocking material is selected from at least one of magnesium oxide, silicon oxide, and aluminum oxide. The pore-blocking material is filled on the end surface of the green body during the high-temperature sintering process to form a wall-flow-like airflow direction when the airflow passes through the interior. The relatively synchronous thermal reaction and synthesis reaction process of the pore-blocking material and the body helps to cause smaller deformation during the sintering process and prevent cracking during the high-temperature sintering process.
[0064] (5) Sintering: The DPF green body to be sintered is placed in a sintering furnace for sintering. A two-stage sintering method and atmosphere-controlled sintering are used to optimize grain growth and reduce defects. During the sintering process, the composite pore former decomposes to form pores; at the same time, the synthetic cordierite raw powder forms a solid skeleton structure, giving the DPF the required mechanical strength and thermal stability, forming a honeycomb structure with the target pore size and porosity.
[0065] (6) Post-processing: The sintered honeycomb ceramics are subjected to a post-processing process of cooling, cutting, purging and cleaning, and a protective coating of room temperature coagulation technology is applied on its periphery to ensure the dimensional accuracy and performance of the DPF product, block excess pores, and ensure that the airflow passes completely through the filter wall.
[0066] In some achievable embodiments, the two-stage sintering method comprises:
[0067] The first stage: low-temperature pre-sintering. The dried DPF green body is placed in a sintering furnace and heated to the pre-sintering temperature at a slow heating rate of (0.08~0.2)°C / min. The pre-sintering temperature is 600°C~900°C and is kept at the pre-sintering temperature for 1h~3h to facilitate the decomposition of the pore former and the escape of gas, reduce the stress inside the green body, and prevent the green body from cracking due to rapid heating. In addition, the initial grain growth in this process lays the foundation for the second stage sintering.
[0068] The second stage: high temperature sintering. After the pre-sintering is completed, continue to heat up to the high temperature sintering temperature at a rapid heating rate of (1~3) °C / min. The high temperature sintering temperature is 1200°C~1400°C and is maintained at high temperature for 4h~10h to achieve full densification of the material, improve the mechanical strength and thermal stability of the DPF, optimize grain growth, reduce grain boundary defects, and improve the overall performance of the material.
[0069] Pre-sintering creates conditions for high-temperature sintering, which enables sufficient grain growth and material densification. The temperature and time of high-temperature sintering need to be precisely controlled to achieve the desired porosity and mechanical strength.
[0070] And / or, after sintering, cool to room temperature at a cooling rate of (0.5~0.8)°C / min.
[0071] In some achievable methods, the atmosphere controlled sintering refers to controlling the atmosphere in the sintering furnace during the sintering process, introducing an inert gas (such as nitrogen or argon) or a reducing atmosphere or a low-oxygen gas discharged after sintering, which can not only prevent the oxidation of the material at high temperature and keep the surface of the material clean and intact, but also promote the uniform growth of the grains, reduce oxygen defects, and improve the electrical and thermal properties of the material. In a reducing atmosphere, it helps to remove impurities in the raw materials and improve the purity and performance of the DPF.
[0072] And / or, the pressure in the sintering furnace is normal pressure or slightly positive pressure.
[0073] Through the combination of the above two-stage sintering and atmosphere-controlled sintering, the quality and performance of DPF products can be significantly improved, defects can be reduced, and production efficiency can be improved.
[0074] In some achievable embodiments, the drying process in step (3) includes:
[0075] (31) Pre-drying: The DPF green body after forming is pre-treated by microwave drying, and the microwave frequency is 2450 MHz to complete the shaping of the DPF green body.
[0076] Specifically, in the present invention, a microwave drying line can be used to dry and shape the formed DPF green body. If hot air drying is used directly, heat conduction will be blocked, and the moisture inside the DPF cannot be discharged. The outside of the DPF is dried, but the inside is still at a low temperature and the moisture cannot be discharged. After the outside is dried, shrinkage will occur, resulting in cracks.
[0077] The first 3 / 5 of the microwave drying line in the present invention is high power (water extraction efficiency is 150kg / h-300kg / h), and the last 2 / 5 of the microwave drying line is low power (water extraction efficiency is 50kg / h-100kg / h). The microwave drying line box is made of microwave leakage-proof stainless steel material, and the top is equipped with an inverted funnel structure water vapor collection and discharge device to prevent steam condensation from generating droplets that fall heavily on the product, and is equipped with a segmented dehumidification system with adjustable frequency.
[0078] For example, a microwave drying line can adopt a five-box structure, with the first three boxes being high power and the rear two boxes being low power, and the total power of the five boxes being 240kw.
[0079] The formed DPF green body is placed in a drying room at room temperature for preliminary air drying. The humidity in the drying room is controlled within the range of 10% to 30%. A low humidity environment is used to reduce cracking caused by water evaporation.
[0080] (32) Heating and drying: After pre-drying, the green body is heated to further remove moisture.
[0081] (33) Isothermal drying: After reaching the set final temperature of 90°C~110°C, keep the temperature for 2h~6h until the moisture in the green body is basically removed. Isothermal drying and uniform airflow ensure that the green body is dried uniformly as a whole, avoiding local overdrying or underdrying.
[0082] In some achievable embodiments, a step-by-step temperature increase mode is used in the temperature increase and drying step, and each stage is maintained for a certain time so that moisture is gradually released.
[0083] Stage 1: Heating to 50°C at a rate of (1-2)°C / min and keeping at that temperature for 0.5h-1h to preliminarily remove free moisture in the material and avoid internal stress in the material caused by rapid heating;
[0084] The second stage: continue to heat up to 100°C at a heating rate of (2~3)°C / min and keep warm for 1h~2h to further remove the moisture adsorbed on the surface of the material.
[0085] The step-wise heating in the present invention helps to reduce cracking of the green body caused by rapid evaporation of water.
[0086] In some achievable embodiments, the cooling process in the post-processing step includes:
[0087] In the initial rapid cooling stage, the sample was rapidly cooled to 65°C at a cooling rate of (2-3)°C / min;
[0088] In the later slow stage, the sample is slowly cooled to room temperature at a cooling rate of (0.1~0.2) °C / min.
[0089] In some achievable methods, after sintering, deionized water or a weak acid solution is used to clean and remove impurities on the surface of the honeycomb ceramic;
[0090] And / or, ultrasonic cleaning is used, the cleaning temperature is controlled at 60-80°C, and the cleaning time is 10-30min;
[0091] In the present invention, the cordierite phase needs to be formed after high-temperature sintering before it can be rinsed with clean water. The unsintered cuttings will absorb moisture and dissolve when they come into contact with water.
[0092] And / or, use a diamond blade or diamond wire cutting for precision cutting.
[0093] In the present invention, on the one hand, by precisely controlling the type and content of the pore former and the grain growth during the sintering process, the pore size can be precisely controlled, thereby meeting the requirement of a median pore diameter of 18um±3um;
[0094] On the other hand, the parameter selection during drying and sintering directly affects the degree of pore former decomposition and gas escape, which in turn affects the porosity. Appropriate drying and sintering conditions can ensure that the target porosity of 55%~65% is achieved.
[0095] In addition, by selecting appropriate raw materials and sintering process, the thermal expansion coefficient of the material (room temperature ~ 800℃) can be controlled to ≤1.0×10 -6 / ℃. Atmosphere controlled sintering also helps reduce defects and improve the thermal stability of the material, thereby achieving low CTE.
[0096] Compared with the prior art, the present invention has the following beneficial effects: (1) The particle collector provided by the present invention meets the requirements of the emission particulate matter control under the new emission regulations (under the WHTC test cycle, ), adjust its pore size and porosity to achieve a 20% reduction in air flow resistance compared to ordinary products on the market, while also taking into account heat shock resistance.
[0097] (2) The composite pore-forming agent used in the present invention can combine the advantages of different pore-forming agents to achieve better performance. Among them, low-density hollow "white carbon black" and unmelted crystalline silica powder can form larger pores, while pregelatinized starch powder and paraffin powder can form smaller pores. By reasonably adjusting the ratio between them, the pore size distribution can be controlled to meet the median pore size requirement of 18um±3um required by the present invention.
[0098] (3) The raw materials and the composition system of the present invention are used to prepare a material with a median pore size of 18um±3um, a porosity of 55%~65%, and a thermal expansion coefficient (room temperature~800℃) ≤1.0×10 -6 / ℃ low back pressure DPF particulate filter. By precisely controlling the ratio of each raw material, the back pressure can be reduced while ensuring the filtration efficiency, and the thermal stability and mechanical strength can be improved, thereby improving the overall performance and reliability of the DPF. The advantage of this ratio is that it can balance the various performance indicators of the DPF, making it perform well in the harsh engine exhaust treatment environment.
[0099] (4) In the present invention, on the one hand, by precisely controlling the type and content of the pore former, as well as the grain growth during the sintering process, the pore size can be precisely controlled, thereby meeting the requirement of a median pore size of 18um±3um; on the other hand, the parameter selection during the drying and sintering process directly affects the degree of pore former decomposition and gas escape, and thus affects the porosity. Appropriate drying and sintering conditions can ensure that the target porosity of 55%~65% is achieved.
[0100] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0101] Figure 1 The structure diagram of the existing wall-flow structure cordierite DPF is shown in FIG. 1 , in which the airflow passes through the inner pore wall of the honeycomb ceramic;
[0102] Figure 2 A schematic diagram of the capture of particulate matter by the pore wall in the existing wall-flow structured cordierite DPF;
[0103] Figure 3 This is a graph showing the heat release characteristics of the composite pore-forming agent in an embodiment of the present invention;
[0104] Figure 4 The TG-DSC diagram of the particle trap body sample prepared in the embodiment of the present invention reflects its thermal stability and decomposition process. The particle trap is in the temperature condition of 0-1400°C and is ventilated with air. The green line reflects its mass change, the blue line reflects its relative heat release, and the blue ordinate is above 0, indicating relative heat absorption.
[0105] Figure 5 The temperature-deformation diagram of the particle collector body samples prepared in Examples 1 to 3 of the present invention and Comparative Example 1 reflects the thermal expansion characteristics thereof, wherein the abscissa represents the temperature of 0 to 1400° C. and the ordinate represents the amount of material change of the sample;
[0106] Figure 6 This is an approximate distribution diagram of the pore size of the particle collector body sample in the embodiment of the present invention, indicating that the pore size is concentrated in the range of 18um±3um, wherein the "pore volume" in the vertical axis refers to the total amount of mercury that can be pressed into the sample during the porosity test, often referred to as the total pore volume. As the pressure increases, the pore volume increases within a certain range. DETAILED DESCRIPTION
[0107] To facilitate understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings, but the present invention can be implemented in different forms and is not limited to the embodiments described in the text. On the contrary, these embodiments are provided to make the content disclosed in the present invention more thorough and comprehensive.
[0108] Embodiment 1: In the first aspect, the present embodiment provides a low back pressure DPF particulate filter with a median pore size of 18um±3um, comprising a particulate filter body and a catalytic coating coated on the particulate filter body, wherein the particulate filter body comprises the following raw materials in mass percentage: 70% synthetic cordierite raw powder, 20% composite pore former (including 10% white carbon black, 7.5% crystalline silicon powder, 1.5% pregelatinized starch powder and 1% paraffin powder), 6% binder (polyvinyl alcohol) and 4% lubricating additive (glycerol).
[0109] In this embodiment, the synthetic cordierite raw powder includes the following raw material components in weight ratio: 35% flaky talc, 20% alpha alumina, 6% activated alumina, 35% kaolin, and 4% silica powder;
[0110] Preferably, in this embodiment, the D50 of the flaky talc is 12 um, the D50 of the alpha alumina is 1 um, the D50 of the activated alumina is 1.5 um, and the D50 of the kaolin is 3 um;
[0111] Preferably, in this embodiment, the activated alumina is diaspore, and the kaolin is washed, flaked, calcined and then used.
[0112] The synthesis steps of the above-mentioned synthetic cordierite raw powder are as follows:
[0113] (1) Raw material preparation: Select flaky talc raw materials with a D50 of 12um~27um, screen and pre-treat them to remove impurities; select alpha alumina raw materials with a D50 of 0.5um~8um to ensure that their quality and particle size meet the requirements;
[0114] Select at least one of diaspore, boehmite or aluminum hydroxide as the raw material of activated alumina according to the needs, control D50 at 1.5um~10um, and inspect the raw materials to ensure their activity;
[0115] The kaolin is washed, peeled and calcined to remove impurities and improve its purity and plasticity; silica micropowder raw materials with appropriate particle size (D50 between 3um and 10um) are selected to ensure its quality.
[0116] (2) Ingredients: Accurately weigh the raw materials according to the weight ratio of 35% of flaky talc, 20% of alpha alumina, 6% of activated alumina, 35% of kaolin and 4% of silica powder, and place them in a clean mixing container.
[0117] (3) Mixing: Use mechanical stirring equipment to fully stir the raw materials at an appropriate speed. The stirring time is determined according to the amount of raw materials and the stirring effect, and is generally not less than 30 minutes to ensure that the raw materials are mixed evenly.
[0118] (4) Pre-reaction: In order to make the raw materials react better, the mixed raw materials can be pre-reacted at a certain temperature (such as 400°C~600°C) for 1~2 hours. This step can promote the initial reaction between the raw materials and is conducive to the subsequent formation of cordierite phase.
[0119] (5) Crushing and grinding: If the material after the pre-reaction has agglomeration phenomenon, it can be crushed and ground to crush the material to the required particle size range to ensure the uniformity of the particle size of the synthetic cordierite raw powder, which is beneficial to the subsequent molding process.
[0120] In a second aspect, an embodiment of the present invention provides a method for preparing a particle collector, comprising the following steps:
[0121] (1) Raw material mixing: Mix the above raw materials evenly according to the proportions.
[0122] (2) Wet molding: Add water to the mixed raw materials to make slurry. The electrical conductivity of the water is less than 0.056us / cm and the moisture content is controlled at 25%. The DPF green body with a certain shape and strength is formed by extrusion molding or compression molding. The molding pressure is ≤10MPa.
[0123] (3) Drying: The DPF green body to be sintered is placed in a drying chamber for drying to remove moisture and prevent cracking or deformation during the subsequent sintering process. Specifically, it includes:
[0124] (31) Pre-drying: The DPF green body after forming is pre-treated by microwave drying, and the microwave frequency is 2450 MHz to complete the shaping of the DPF green body.
[0125] Specifically, in the present invention, a microwave drying line can be used to dry and shape the formed DPF green body. If hot air drying is used directly, heat conduction will be blocked, and the moisture inside the DPF cannot be discharged. The outside of the DPF is dried, but the inside is still at a low temperature and the moisture cannot be discharged. After the outside is dried, shrinkage will occur, resulting in cracks.
[0126] In the present invention, the first 3 / 5 of the microwave drying line is high power, the last 2 / 5 of the microwave drying line is low power, and the microwave drying line is equipped with a segmented dehumidification system with adjustable frequency.
[0127] For example, a microwave drying line can adopt a five-box structure, with the first three boxes being high power and the rear two boxes being low power, and the total power of the five boxes being 240kw.
[0128] (32) Heating and drying: After pre-drying, the green body is slowly heated to further remove moisture. The heating and drying step uses a step-by-step heating mode. In the first stage, the temperature is raised to 50°C at a heating rate of 1°C / min and kept at this temperature for 0.5h to preliminarily remove free moisture in the material and avoid internal stress in the material caused by rapid heating;
[0129] The second stage: continue to heat up to 100°C at a heating rate of 3°C / min and keep warm for 1h to further remove the moisture adsorbed on the surface of the material.
[0130] (33) Isothermal drying: After reaching the set final temperature of 110 °C, keep the temperature for 5 h until the moisture in the green body is basically removed.
[0131] After drying, the DPF green body is preliminarily processed into regular size, and then the holes are blocked at its two end faces. A carbon dioxide laser source is used to identify the low-viscosity, high-transmittance resin tape sealed on the end face and then make holes at intervals. The above-mentioned plugging material is "scraped" into the hole with a depth of 3.5mm~7mm to form the DPF green body to be sintered.
[0132] (4) Hole plugging: After drying, the DPF green body is preliminarily processed into regular size, and then the hole plugging material is used to cross-plug the holes on its two end faces. A carbon dioxide laser source is used to identify the low-viscosity, high-transmittance resin tape sealed on the end face and then separate the holes. The above-mentioned hole plugging material is "scraped" into the hole with a depth of 3.5mm~7mm to form a DPF green body to be sintered.
[0133] In some achievable methods, the pore plugging material is selected from at least one of magnesium oxide, silicon oxide, and aluminum oxide. The pore plugging material is filled in the holes formed by the pore forming agent during the high-temperature sintering process to adjust the pore size distribution on the surface of the particle trap, improve the material strength and thermal stability, and prevent the DPF from deforming and breaking in a high-temperature environment. Specifically, in this embodiment, the pore plugging material is magnesium oxide.
[0134] (5) Sintering: A two-stage sintering process is adopted. The first stage is low-temperature pre-sintering. The dried DPF green body is placed in a sintering furnace and slowly heated to the pre-sintering temperature at a rate of 0.2°C / min. The pre-sintering temperature is 800°C and kept at the pre-sintering temperature for 1h.
[0135] The second stage: high temperature sintering. After the pre-sintering is completed, the temperature is continuously increased at a rapid heating rate of 3°C / min to the high temperature sintering temperature, the high temperature sintering temperature is 1200°C, and maintained at high temperature for 5 hours.
[0136] During the sintering process, the atmosphere in the sintering furnace is controlled, an inert gas is introduced into the sintering furnace, and the pressure in the sintering furnace is controlled to be normal pressure.
[0137] After sintering, the sample was cooled to room temperature at a cooling rate of 0.8-1.4°C / min.
[0138] (6) Post-processing: The sintered honeycomb ceramic is subjected to a post-processing process of cooling, cutting, purging and cleaning, and a protective coating of room temperature coagulation technology is coated on its periphery to ensure the dimensional accuracy and performance of the DPF product, block the redundant pores, and ensure that the airflow completely passes through the filter wall. Specifically, in this embodiment, a diamond blade or diamond wire cutting is used for precise cutting, and deionized water is used to clean and remove impurities on the surface of the honeycomb ceramic.
[0139] The cooling process includes: an initial rapid cooling stage, rapidly cooling to 65°C at a cooling rate of 2°C / min; and a later slow stage, slowly cooling to room temperature at a cooling rate of 0.1°C / min.
[0140] Example 2: The preparation method of this example is consistent with that of Example 1, except that, during the sintering process, the first stage: low-temperature pre-sintering, the dried DPF green body is placed in a sintering furnace, and the temperature is slowly increased at a rate of 0.08°C / min to a pre-sintering temperature of 600°C, and the temperature is kept at the pre-sintering temperature for 1h;
[0141] The second stage: high temperature sintering. After the pre-sintering is completed, the temperature is slowly increased at a rate of 1°C / min to the high temperature sintering temperature, which is 1400°C, and maintained at high temperature for 4 hours.
[0142] The formula of the particle collector body in this embodiment is consistent with that in Embodiment 1, and the raw material formula of cordierite is also consistent with that in Embodiment 1.
[0143] Example 3: The preparation method of this example is consistent with that of Example 1, except that the parameters of the step-wise heating mode in the heating and drying step are different. Specifically, in the first stage, the temperature is slowly increased to 50°C at a heating rate of 1.5°C / min, and the temperature is kept for 1h to preliminarily remove free moisture in the material and avoid internal stress of the material caused by rapid heating;
[0144] The second stage: continue to heat up to 100°C at a slow heating rate of 2°C / min and keep warm for 1h to further remove the moisture adsorbed on the surface of the material.
[0145] The formula of the particle collector body in this embodiment is consistent with that in Embodiment 1, and the raw material formula of cordierite is also consistent with that in Embodiment 1.
[0146] Example 4: The preparation method of this example is consistent with that of Example 1, except that the particle collector body includes the following raw materials in percentage by mass: 75% synthetic cordierite raw powder, 20% composite pore former (including 10% white carbon black, 7.5% crystalline silicon powder, 1.5% pregelatinized starch powder and 1% paraffin powder), 4% binder (polyvinyl alcohol) and 1% lubricating additive (glycerol).
[0147] The raw material formula of the synthetic cordierite raw powder in this example is consistent with that in Example 1.
[0148] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0149] Example 5: The preparation method of this example is consistent with that of Example 1, except that the particle collector body includes the following raw materials in percentage by mass: 75% synthetic cordierite raw powder, 15% composite pore former (including 7.5% white carbon black, 5.625% crystalline silicon powder, 1.125% pregelatinized starch powder and 0.75% paraffin powder), 5% binder (polyvinyl alcohol) and 5% lubricating additive (glycerol).
[0150] The raw material formula of the synthetic cordierite raw powder in this example is consistent with that in Example 1.
[0151] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0152] Example 6: The preparation method of this example is consistent with that of Example 1, except that the particle collector body includes the following raw materials in percentage by mass: 80% synthetic cordierite raw powder, 15% composite pore-forming agent (including 7.5% white carbon black, 5.625% crystalline silicon powder, 1.125% pregelatinized starch powder and 0.75% paraffin powder), 3% binder (polyvinyl alcohol) and 2% lubricating additive (glycerol).
[0153] The raw material formula of the synthetic cordierite raw powder in this example is consistent with that in Example 1.
[0154] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0155] Example 7: The formula of the particle collector body in this example is basically the same as that in Example 1, except that the synthetic cordierite raw powder in this example includes the following raw material components in weight ratio: 40% flaky talc, 15% alpha alumina, 7% activated alumina, 35% kaolin, and 3% silica powder;
[0156] Preferably, in this embodiment, the D50 of the flaky talc is 12 um, the D50 of the alpha alumina is 1 um, the D50 of the activated alumina is 1.5 um, and the D50 of the kaolin is 3 um;
[0157] Preferably, in this embodiment, the activated alumina is diaspore, and the kaolin is washed, flaked, calcined and then used.
[0158] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0159] Example 8: The formula of the particle collector body in this example is basically the same as that in Example 1, except that the synthetic cordierite raw powder in this example includes the following raw material components in weight ratio: 38% flaky talc, 18% alpha alumina, 5% activated alumina, 35% kaolin, and 4% silica powder;
[0160] In this embodiment, the D50 of the flaky talc is 12 um, the D50 of the alpha alumina is 1 um, the D50 of the activated alumina is 1.5 um, and the D50 of the kaolin is 3 um;
[0161] In this embodiment, diaspore is selected as the activated alumina, and the kaolin is washed, peeled and calcined before use.
[0162] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0163] Example 9: The formula of the particle collector body in this example is basically the same as that in Example 1, except that the synthetic cordierite raw powder in this example includes the following raw material components in weight ratio: 35% flaky talc, 20% alpha alumina, 6% activated alumina, 35% kaolin, and 4% silica powder;
[0164] In this embodiment, the D50 of the flaky talc is 20 um, the D50 of the alpha alumina is 8 um, the D50 of the activated alumina is 3 um, and the D50 of the kaolin is 2.5 um;
[0165] In this embodiment, the activated alumina is aluminum hydroxide, and the kaolin is washed, peeled, calcined and then used.
[0166] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0167] Example 10: The formula of the particle collector body in this example is basically the same as that in Example 1, except that the synthetic cordierite raw powder in this example includes the following raw material components in weight ratio: 35% flaky talc, 20% alpha alumina, 6% activated alumina, 35% kaolin, and 4% silica powder;
[0168] Preferably, the D50 of the flaky talc is 27um, the D50 of alpha alumina is 0.5um, the D50 of activated alumina is 10um, and the D50 of kaolin is 7.5um;
[0169] In this embodiment, the activated alumina is aluminum hydroxide, and the kaolin is washed, peeled, calcined and then used.
[0170] The process steps and parameters of the preparation method of the particle collector of this embodiment are consistent with those of Example 1.
[0171] Comparative Example 1: The particle collector in this comparative example is consistent with that in Example 1, except that the particle collector body includes the following raw materials in percentage by mass: 70% synthetic cordierite raw powder, 20% white carbon black pore former, 6% binder (polyvinyl alcohol) and 4% lubricating additive (glycerol).
[0172] The pore size of the particle collector prepared in this comparative example is controlled within the pore size range of 22um~26um, the porosity is 51.2%, and the thermal expansion coefficient (room temperature~800℃) is 1.156×10 -6 / ℃, the back pressure is 6.5dynes / cm²; the coating amount of the reducing catalyst in the catalytic coating is 200g / L.
[0173] The raw material formula of cordierite in this comparative example is consistent with that in Example 1.
[0174] The preparation method of the particle collector of this comparative example adopts the existing conventional process.
[0175] Comparative Example 2: The preparation method in this comparative example is basically consistent with that in Example 1, except that the two-stage sintering method is not adopted, and the temperature is raised from room temperature to 1200° C. and maintained for 4 to 6 hours.
[0176] The pore size of the particle collector prepared in this comparative example is controlled within the pore size range of 14um~16um, the porosity is 68.6%, and the thermal expansion coefficient (room temperature~800℃) is 1.225×10 -6 / ℃, the back pressure is 3.8dynes / cm²; the coating amount of the reducing catalyst in the catalytic coating is 200g / L.
[0177] The formula of the particle collector body in this comparative example is consistent with that in Example 1, and the raw material formula of cordierite is also consistent with that in Example 1.
[0178] Comparative Example 3: The preparation method in this comparative example is basically consistent with that in Example 1, except that no staged drying process is adopted. In this comparative example, the drying temperature is controlled at 100°C and the drying time is 24h.
[0179] The pore size of the particle collector prepared in this comparative example is controlled within the pore size range of 15um~17um, the porosity is 65.3%, and the thermal expansion coefficient (room temperature~800℃) is 0.995×10 -6 / ℃, the back pressure is 4.2dynes / cm²; the coating amount of the reducing catalyst in the catalytic coating is 200g / L.
[0180] The formula of the particle collector body in this comparative example is consistent with that in Example 1, and the raw material formula of cordierite is also consistent with that in Example 1.
[0181] Comparative Example 4: The formula of the particle collector body in this comparative example is basically the same as that in Example 1, except that the cordierite in this example includes the following raw material components in weight ratio: 30% flaky talc, 35% alpha alumina, 12% activated alumina, 15% kaolin, and 8% silica powder;
[0182] In this comparative example, the D50 of the flaky talc is 30 um, the D50 of the alpha alumina is 10 um, the D50 of the activated alumina is 5 um, and the D50 of the kaolin is 8 um;
[0183] In this comparative example, diaspore is used as the activated alumina, and the kaolin is not treated.
[0184] The process steps and parameters of the preparation method of the particle collector of this comparative example are consistent with those of Example 1.
[0185] The pore size of the particle collector prepared in this comparative example is controlled within the pore size range of 19um~21um, the porosity is 58.2%, and the thermal expansion coefficient (room temperature~800℃) is 1.05×10 -6 / ℃, the back pressure is 5.5dynes / cm²; the coating amount of the reducing catalyst in the catalytic coating is 200g / L.
[0186] Comparative Example 5: The formula of the particle collector body in this comparative example is basically the same as that in Example 1, except that the cordierite in this example includes the following raw material components in weight ratio: 50% flaky talc, 10% alpha alumina, 18% activated alumina, 20% kaolin, and 2% silica powder;
[0187] In this comparative example, the D50 of the flaky talc is 10 um, the D50 of the alpha alumina is 2 um, the D50 of the activated alumina is 12 um, and the D50 of the kaolin is 2 um;
[0188] In this comparative example, diaspore is used as the activated alumina, and the kaolin is not treated.
[0189] The process steps and parameters of the preparation method of the particle collector of this comparative example are consistent with those of Example 1.
[0190] The pore size of the particle collector prepared in this comparative example is controlled within the pore size range of 20um~22um, the porosity is 55.1%, and the thermal expansion coefficient (room temperature~800℃) is 1.10×10 -6 / ℃, the back pressure is 6.0dynes / cm²; the coating amount of the reducing catalyst in the catalytic coating is 200g / L.
[0191] Table 1 is a performance analysis table of DPF in Examples 1 to 10 and Comparative Examples 1 to 5
[0192] Example / Comparative Example Aperture (um) Porosity (%) <![CDATA[CTE(30-800℃)(10 -6 / ℃)]]> Back pressure (dynes / cm²) Example 1 18±3 60.9 0.985 4.0 Example 2 18±3 62.6 0.996 3.8 Example 3 18±3 59.8 0.972 4.2 Example 4 18±3 63.5 0.986 3.9 Example 5 18±3 61.1 0.992 3.8 Example 6 18±3 62 0.978 3.7 Example 7 18±3 60.5 0.982 4.1 Example 8 18±3 60.8 0.988 4.0 Example 9 18±3 60.3 0.980 4.3 Example 10 18±3 61.6 0.984 4.2 Comparative Example 1 22~26 51.2 1.156 6.5 Comparative Example 2 14~16 68.6 1.225 3.8 Comparative Example 3 15~17 65.3 0.995 4.2 Comparative Example 4 19~21 58.2 1.05 5.5 Comparative Example 5 20~22 55.1 1.10 6.0
[0193] From the analysis in Table 1, it can be seen that the median pore size of the particle trap body in Examples 1 to 6 is controlled within the range of 18um±3um, the porosity is between 55% and 65%, and the thermal expansion coefficient (room temperature to 800℃) is ≤1.0×10 -6 / ℃, the back pressure is between 3.6 and 4.3dynes / cm², meeting the requirement of low back pressure.
[0194] In general, the embodiments have better performance in pore size, porosity, thermal expansion coefficient and back pressure, etc., compared with the comparative examples, by optimizing the formula and preparation process. For example, the porosity in Examples 1 to 10 is generally high, which is conducive to gas circulation, thereby reducing the back pressure; the thermal expansion coefficient is low, the structural stability is good, and it is also helpful to maintain a low back pressure.
[0195] Different process parameter adjustments have different effects on performance. For example, in the sintering process, after the sintering parameters are changed in Example 2, the porosity and other properties change, and the back pressure also changes accordingly; in the drying process, after the drying parameters are changed in Example 3, the porosity decreases and the back pressure increases.
[0196] Changes in raw material formulas can also affect performance. Examples 4-6 adjust the raw material formula ratio of the particle collector body, and Examples 7-10 change the cordierite raw material component ratio and the D50 value of some raw materials, which all affect the porosity, thermal expansion coefficient, etc., and thus affect the back pressure.
[0197] Comparative Example 1 has poor performance and high back pressure due to the use of a single pore former and conventional process; Comparative Example 2 does not use a two-stage sintering method, Comparative Example 3 does not use a staged drying process, and Comparative Examples 4 and 5 have different cordierite raw material treatments.
[0198] Therefore, the median pore size of Comparative Example 1 exceeds the target range, the porosity is lower than the lower limit, the thermal expansion coefficient and the back pressure are higher than the embodiment, and the performance requirements are not met; the median pore size of Comparative Example 2 is lower than the target range, the porosity is higher than the upper limit, and the thermal expansion coefficient and the back pressure do not meet the requirements; the median pore size of Comparative Example 3 exceeds the target range, although the porosity and the thermal expansion coefficient are within the range, and the low back pressure requirements are met, but this is at the expense of the pore size.
[0199] From these data, we can see that by precisely controlling the raw material ratio and the preparation process parameters, a DPF particulate filter that meets specific performance requirements can be prepared. The data of the above examples and comparative examples show the sensitivity of the raw material ratio and the process parameters to the DPF performance, and the above parameters need to be precisely controlled during the production process.
[0200] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A particle trap, comprising a particle trap body and a catalytic coating coated on the particle trap body, characterized in that: The particle collector body comprises the following raw materials in percentage by mass: 70% to 80% of synthetic cordierite raw powder, 15% to 20% of composite pore former, 2% to 6% of binder and 1% to 5% of lubricating additive; The composite pore-forming agent includes white carbon black, crystalline silicon powder, pregelatinized starch powder and paraffin powder, and the ratio of white carbon black, crystalline silicon powder, pregelatinized starch powder and paraffin powder is 10:7.5:1.5:1; The pore size of the particle collector body is controlled within the median pore size range of 18um±3um, the porosity is 55%~65%, and the thermal expansion coefficient is ≤1.0×10 ~6 / ℃.
2. The particle collector according to claim 1, characterized in that: The coating amount of the reducing catalyst in the catalytic coating is 120 g / L to 220 g / L.
3. The particle collector according to claim 1, characterized in that: The synthetic cordierite raw powder comprises the following raw material components in weight ratio: Talc flakes 35%~45%, alpha alumina 15%~25%, activated alumina 1%~10%, kaolin 20%~40%, silica powder 3%~10%; The D50 of the flaky talc is 12um~27um, the D50 of alpha alumina is 0.5um~8um, the D50 of activated alumina is 1.5um~10um, and the D50 of kaolin is 2.5um~7.5um; The activated alumina may be selected from at least one of diaspore, boehmite and aluminum hydroxide; The kaolin is washed, peeled and calcined before use.
4. The particle collector according to any one of claims 1 to 3, characterized in that: The binder is selected from at least one of anionic polyvinyl alcohol and hydroxypropyl methylcellulose; And / or, the lubricating additive is at least one of glycerol, potassium laurate and sodium stearate.
5. A method for preparing a particle collector, characterized in that: For preparing the particle collector according to any one of claims 1 to 4, the preparation method comprises the following steps: (1) Raw material mixing: mixing synthetic cordierite raw powder, composite pore-forming agent, binder and lubricating additive according to the proportion; (2) Wet molding: Add an appropriate amount of water to the mixed raw materials, stir evenly to form a mud mass, and then form the DPF green body by extrusion or pressing, in which the moisture content is controlled at 20%~30%; (3) Drying: The formed DPF green body is placed in a drying chamber for drying to remove moisture and prevent cracking or deformation during the subsequent sintering process; (4) Pore plugging: After drying, the DPF green body is preliminarily processed, and then the two end surfaces are cross-plugged using the plugging material; (5) Sintering: The DPF green body to be sintered after the pores are plugged is placed in a sintering furnace for sintering, and a two-stage sintering method and atmosphere-controlled sintering are combined to optimize grain growth and reduce defects; The two-stage sintering method comprises: The first stage: low-temperature pre-sintering, the dried DPF green body is placed in a sintering furnace, and the temperature is slowly increased at a rate of 0.08°C / min to 0.2°C / min to the pre-sintering temperature of 600°C to 900°C, and the temperature is kept at the pre-sintering temperature for 1h to 3h; The second stage: high temperature sintering. After the pre-sintering is completed, the temperature is continuously raised at a rapid heating rate of 1°C / min~3°C / min to the high temperature sintering temperature. The high temperature sintering temperature is 1200°C~1400°C and maintained at high temperature for 4h~10h. (6) Post-processing: The sintered honeycomb ceramics undergo post-processing processes such as cooling, cutting, purging and cleaning, and a protective coating using room temperature coagulation technology is applied on its periphery.
6. The method for preparing a particle collector according to claim 5, characterized in that: The atmosphere controlled sintering refers to controlling the atmosphere in the sintering furnace during the sintering process, and introducing an inert gas or a reducing atmosphere or a low-oxygen gas exhausted after sintering into the sintering furnace; The pressure in the sintering furnace is normal pressure or slightly positive pressure.
7. The method for preparing a particle collector according to claim 5 or 6, characterized in that: The drying process in step (3) includes: (31) pre-drying, pre-treating the formed DPF green body by microwave drying, with a microwave frequency of 2450 MHz, to complete the shaping of the DPF green body; (32) Heating and drying: after pre-drying, the green body is slowly heated to further remove moisture; (33) Isothermal drying: After reaching the set final temperature of 90°C~110°C, keep the temperature for 2h~6h until the moisture in the green body is basically removed.
8. The method for preparing a particle collector according to claim 7, characterized in that: The step-by-step heating mode is used in the heating and drying step. In the first stage, the temperature is raised to 50°C at a heating rate of 1°C / min to 2°C / min, and the temperature is kept for 0.5h to 1h to preliminarily remove free moisture in the material and avoid internal stress of the material caused by rapid heating. The second stage: continue to heat up to 100°C at a heating rate of 2°C / min~3°C / min, and keep warm for 1h~2h to further remove the moisture adsorbed on the surface of the material.
9. The method for preparing a particle collector according to claim 5, characterized in that: The cooling process in the post-processing step includes: In the initial rapid cooling stage, the temperature is rapidly cooled to 65°C at a cooling rate of 2°C / min~3°C / min; In the later slow stage, the sample is slowly cooled to room temperature at a cooling rate of 0.1°C / min~0.2°C / min.
10. The method for preparing a particle collector according to claim 5 or 9, characterized in that: Use deionized water or weak acid solution to clean and remove impurities on the surface of honeycomb ceramics; And / or, ultrasonic cleaning is used, the cleaning temperature is controlled at 60°C to 80°C, and the cleaning time is 10min to 30min; And / or, use a diamond blade or diamond wire cutting for precision cutting.
Citation Information
Patent Citations
Method for preparing gasoline vehicle particle catcher by using fumed silica
CN109650934A
Cordierite gasoline engine particulate filter and preparation method thereof
CN113860852A
Method for drying ceramic molded article
JP1997077552A
Ceramic porous body and method for producing the same, and dust collecting filter
US20200306742A1